EFEKTIVITAS DESENTRALISASI MANAJEMEN PENDIDIKAN ANAK USIA DINI (PAUD) - Supriadi, Oding (TABULARASA, 2014)
Early age (age 0-6 years) widely seen as the age or the golden years of growth and development of children (the golden age / years). At that age, vital time occurs, namely, the need to touch the beginning of education, appropriate stimulation and sensitive period of growth and development of children. So far the management of early childhood education (ECD) is deemed ineffective. This article explores the idea of decentralized management rather the main purpose of early childhood education early childhood education can be achieved as the positive impact generated and is expected to contribute ideas in the future, especially how to increase community participation in early childhood.